The cultural work of empire : the seven years' war and the imagining of the Shandean State - Watts, Carol, 1962- (UPSO - Edinburgh University Press E-Books., 2007)
This book argues that the Seven Years' War (1756-63) produced an intense historical consciousness within British cultural life regarding the boundaries of belonging to community, family and nation. Global warfare prompts a radical re-imagining of the state and the subjectivities of those who inhabit it. Laurence Sterne's distinctive writing provides a remarkable route through the transformations of mid-eighteenth-century British culture. The risks of war generate unexpected freedoms and crises in the making of domestic imperial subjects, which will continue to reverberate in anti-slavery struggles and colonial conflict from America to India. The book concentrates on the period from the 1750s to the 1770s. It explores the work of Johnson, Goldsmith, Walpole, Burke, Scott, Wheatley, Sancho, Smollett, Rousseau, Collier, Smith and Wollstonecraft alongside Sterne's narratives. It incorporates debates among moral philosophers and philanthropists, examines political tracts, poetry and grammar exercises, and paintings by Kauffman, Hayman, and Wright of Derby, tracking the investments in, and resistances to, the cultural work of empire. Key Features Topical in its focus on the making of 'modern' subjectivity during the first 'global war' Path-breaking in advancing our understanding of the cultural history of eighteenth-century Britain Timely in its combination of new historical research with a critical engagement with debates in postcolonial and subaltern studies Original in its account of the literature of the Seven Years' War and its outstanding analysis of the writing of Laurence Sterne